2017
DOI: 10.1159/000486166
|View full text |Cite
|
Sign up to set email alerts
|

Astragaloside IV Prevents Cardiac Remodeling in the Apolipoprotein E-Deficient Mice by Regulating Cardiac Homeostasis and Oxidative Stress

Abstract: Background: Hypercholesterolemia is a risk factor for the development of cardiac hypertrophy. Astragaloside IV (AST-IV) possesses cardiovascular protective properties. We hypothesize that AST-IV prevents cardiac remodeling with hypercholesterolemia via modulating tissue homeostasis and alleviating oxidative stress. Methods: The ApoE-/- mice were treated with AST-IV at 1 or 10 mg/kg for 8 weeks. The blood lipids tests, echocardiography, and TUNEL were performed. The mRNA expression profile was detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…As-IV has also been reported to inhibit ROS and NADPH production by upregulating PGC-1 α and TFAM, as well as to promote mitochondrial autophagy and mitochondrial biogenesis, contributing to the protection of damaged mitochondria through its antioxidant activity [ 135 ]. As-IV can also reduce the activities of CPK and LDH, reduce the loss of mitochondrial membrane potential, and ultimately slow down cardiomyocyte apoptosis [ 136 138 ].…”
Section: Application Of Antioxidant Natural Drugs For Cardiovasculmentioning
confidence: 99%
“…As-IV has also been reported to inhibit ROS and NADPH production by upregulating PGC-1 α and TFAM, as well as to promote mitochondrial autophagy and mitochondrial biogenesis, contributing to the protection of damaged mitochondria through its antioxidant activity [ 135 ]. As-IV can also reduce the activities of CPK and LDH, reduce the loss of mitochondrial membrane potential, and ultimately slow down cardiomyocyte apoptosis [ 136 138 ].…”
Section: Application Of Antioxidant Natural Drugs For Cardiovasculmentioning
confidence: 99%
“…Moreover, the specific protective effects of ASIV may oppose processes such as cardiomyocyte hypertrophy, apoptosis, and fibrosis [1822]. Some studies have suggested that the protective effect of ASIV against cardiac hypertrophy is related to the regulation of cardiac-related signaling pathways, such as inhibition of the TLR4/NF- κ B signaling pathway and the Ca 2+ /CaN signaling pathway and regulation of NF- κ B/PGC-1 α signaling-mediated energy biosynthesis [18, 19, 23, 24]. Other studies have shown that ASIV can protect brain tissue by reducing oxidative stress and mediating related signaling pathways [25].…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, Apoe possesses anti-inflammatory, anti-oxidative and anti-apoptosis properties (Laskowitz et al, 1997 , 1998 ; Kitagawa et al, 2002 ; Hayashi et al, 2009 ; Li X.-Z. et al, 2017 ). For instance, APOE mimetic peptide significantly suppressed microglial activation in rats with SCI.…”
Section: Introductionmentioning
confidence: 99%